أمريه 07 مارس 1944م والمعالجة الديغولية للمسألة الجزائرية - مدور, خميسة (جامعة الوادي - University of Eloued, 2022)
عالج قانون السيناتيس كونسيلت الصادر بتاريخ 14جويلية 1865م الوضعية القانونية للجزائريين لأول مرة حيث اعتبرت المادة الأولى من هذا القانون الجزائريين المسلمين رعايا فرنسيين بشرط تخليهم عن أحوالهم الشخصية الإسلامية، وهو ما رفضه الجزائريون بشكل قاطع منددين بسياسة التجنيس الفردية، ثم بادرت السلطات الاستعمارية بعد ذلك إلى إصدار مجموعة من النصوص القانونية في محاولة منها لمعالجة هذه الإشكالية العويصة، خاصة بعد صدور مرسوم التجنيس الجماعي ليهود الجزائر أو ما يعرف بمرسوم "كريميو"، ولعل من أبرز هذه النصوص أمريه 07 مارس 1944م التي أصدرها الجنرال ديغول، في ظل ظروف خاصة شهدتها يومئذ فرنسا والجزائر على حد سواء. .....سأحاول في هذا السياق دراسة وتحليل ملابسات إصدار هذه الأمرية، وتحليل مضامينها وبيان علاقتها بما سبقها من قوانين ومشاريع قوانين، بالإضافة الى أهم المراسيم المكملة لنص الامرية و التي حاولت معالجة إشكالية المواطنة الفرنسية بالنسبة للمسلمين الجزائريين وذلك بالاعتماد على مادة أرشيفية من أرشيف ماوراء البحار بمدينة –أكس اون بروفنس - للوقوف خاصة على المشاريع المقدمة لصياغة النص النهائي لهذه الامرية، وكذللك تحليل الوثائق، المراسلات، والتقارير التي عكست موقف الجزائريين المسلمين والمستوطنين على حد السواء، بهدف الاجابة عن السؤال الجوهري الآتي:- ما الجديد الذي تضمنته أمرية 07 مارس 1944م، وهل أفلح الجنرال ديغول من خلالها في حل المعضلة الأهلية؟.. ...The Senatis Consult law issued on July 14, 1865 addressed the legal status of Algerians for the first time, as the first article of this law considered Algerian Muslims French nationals on condition that they renounce their Islamic personal status, which the Algerians rejected. They categorically denounced the policy of individual naturalization, and then the colonial authorities issued a series of legal texts in an attempt to address this difficult problem, especially after the issuance of the decree of collective naturalization of Algerian Jews or the so-called "Cremio" decree, perhaps from The most prominent of these texts is the March 07, 1944 order issued by General de Gaulle, under special circumstances witnessed at that time by both France and Algeria. In this context, I will try to study and analyze the circumstances of the issuance of this order, analyze its contents and indicate its relationship with the previous laws and draft bills, in addition to the most important decrees supplementing the text of the order , which tried to address the problem of French citizenship for Algerian Muslims by relying on an archival material from the Overseas Archives in the city of - Aix-en-Provence - to find out in particular the projects submitted to draft the final text of this order, such as the analysis of documents, correspondence, and reports that reflect the position of Algerian Muslims and settlers alike, in order to answer the fundamental question: - What is new in the order of March 07, 1944, and did General de Gaulle succeeded through it in solving the civil dilemma?
مقال
Keywords: الامرية، مشاريع القوانين، التجنيس، الوضعية القانونية، الأحوال الشخصية، الأهالي، المسلمون الجزائريون، الحقوق المدنية، المواطنة الفرنسية، القضية الجزائرية، الجنيرال ديغول